Persepsi Mahasiswa Universitas Islam Negeri Sunan Kalijaga terhadap Kasus Kekerasan Seksual di Lingkungan Kampus - Muthia Meilani; Nabila Nuurussyifa; Dzulfikri Muhammad; Winny Ashari Zalmi; Ahmad Sunu Aji (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2025)
Sexual violence is a serious problem that has not been resolved optimally. In 2024, the number of sexual violence cases in Indonesia reached 25,314 cases, of which 1,548 of them occurred in the campus environment. Therefore, this problem must be addressed immediately by all universities, including UIN Sunan Kalijaga Yogyakarta. As a religious-based higher education institution, UIN Sunan Kalijaga is responsible for upholding morals and creating a safe environment for the entire academic community. However, in reality, this has not been realized optimally. This raises a big question regarding the extent of students' understanding of this issue. Therefore, a study of this issue is important because students are one of the groups that are very vulnerable to sexual violence. The purpose of this study is to identify the perceptions of UIN Sunan Kalijaga students towards cases of sexual violence in the campus environment. This research uses a survey method by distributing questionnaires through Google Forms with 100 respondents from 21,682. The theory used in this research is the Theory of Public Identification (STP). Based on the results of the TCR test show that respondents have a high awareness of the issue of sexual violence, and most respondents also understand the importance of preventing and handling this issue. However, there is also a gap in reporting this issue. Keywords: Perception, Sexual Violence, Campus, College Student